LA INDUSTRIA AUDIOVISUAL ANTE EL DESPLIEGUE DEL 5G: EL CASO DE LA UNIÓN EUROPEA - Dra. Carmina CRUSAFON, (Fonseca, Journal of Communication, 2023)
The arrival of 5G technology will have a significant impact on the audiovisual industry, especially in the television field. The analysis of the European case highlights the relevance of spectrum management in digital policies. This article explains how the European policy for the deployment of 5G has been de-signed with the creation of a consortium where the main actors of the digital ecosystem participate. It also analyzes the future scenarios which the audiovisual sector must meet. Everything seems to indicate that the year 2025 will be the date on which a significant change could take place, especially in the scenario of dig-ital terrestrial television.